Comparative immunogenicity of monovalent and bivalent adenovirus vaccines carrying spikes of early and late SARS-CoV-2 variants - Hengchun Li; Chenchen Yang; Li Yin; Wenming Liu; Zhengyuan Zhang; Bo Liu; Xinxin Sun; Wenhao Liu; Zihan Lin; Zijian Liu; Ping He; Ying Feng; et al. (Emerging Microbes and Infections)
The continuous emergence of highly immune-evasive SARS-CoV-2 variants has challenged vaccine efficacy. A vaccine that can provide broad protection is desirable. We evaluated the immunogenicity of a series of monovalent and bivalent adenovirus-vectored vaccines containing the spikes of Wildtype (WT), Beta, Delta, Omicron subvariants BA.1, BA.2, BA.2.12.1, BA.2.13, BA.3, BA.5, BQ.1.1, and XBB. Vaccination in mice using monovalent vaccines elicited the highest neutralizing titers against each self-matched strain, but against other variants were reduced 2− to 73-fold. A bivalent vaccine consisting of WT and BA.5 broadened the neutralizing breadth against pre-Omicron and Omicron subvariants except XBB. Among bivalent vaccines based on the strains before the emergence of XBB, a bivalent vaccine consisting of BA.2 and BA.5 elicited the most potent neutralizing antibodies against Omicron subvariants, including XBB. In mice primed with injected WT vaccine, intranasal booster with a bivalent vaccine containing XBB and BA.5 could elicit broad serum and respiratory mucosal neutralizing antibodies against all late Omicron subvariants, including XBB. In mice that had been sequentially vaccinated with WT and BA.5, intranasal booster with a monovalent XBB vaccine elicited greater serum and mucosal XBB neutralizing antibodies than bivalent vaccines containing XBB. Both monovalent and bivalent XBB vaccines induced neutralizing antibodies against EG.5. Unlike the antibody response, which is highly variant-specific, mice receiving either monovalent or bivalent vaccines elicited comparable T-cell responses against all variants. Furthermore, intranasal but not intramuscular booster induced antigen-specific lung resident T cells. This study provides insights into the design of the COVID-19 vaccine and vaccination strategies.